Spirulina Cultivation Using Biogas CO2 as the Carbon Source: Preliminary Study on Biomass Growth and Productivity - Kumar Oruganti Raj; Kumar Kumara Madhu; Tejavath Rakesh; Sriariyanun Malinee; Bhattacharyya Debraj (E3S Web of Conferences, 2023)
Anthropogenic activities are causing a rapid increase in global carbon dioxide (CO2) emissions, which significantly contribute to global warming. Microalgae can be a sustainable solution for simultaneous wastewater treatment and sequestering CO2 through photosynthesis. The current study reports a comparative evaluation of Spirulina sp. microalgal biomass growth and lipid productivity during its cultivation supplied with air and biogas from an anaerobic digester. It was observed that there was a 4-fold increase in biomass productivity in the reactor sparged with biogas compared to air supply. The reactor sparged with biogas showed a significant increase in lipid content. This increase in biomass productivity could be attributed to the increased availability of CO2, favoring algal growth.